Epigenetics of B Cells and Antibody Responses - Paolo Casali (Frontiers Research Topics, 2016)
Epigenetics is the study of changes in gene activity that are heritable but not caused by changes in the DNA sequence. By modulating gene activities, epigenetic changes regulate cell functions. They include DNA methylation, histone posttranslational modifications and gene silencing by the action of non-coding RNAs, particularly microRNAs. It is now clear that epigenetic changes regulate B cell development. By acting in concert with networks of transcription factors, they modulate the activation of B cell lineage specific gene programs and repress inappropriate gene transcription in particular B cell differentiation states. A hallmark of B cell development in the bone marrow is the assembly of the B cell receptor (BCR) for antigen through rearrangement of immunoglobulin heavy (IgH) and light (IgL) chain V(D)J genes, as mediated by RAG1/RAG2 recombinases. Ig V(D)J rearrangement critically times the progression from pro-B cell to pre-B cell and, finally, mature B cell. Such progression is modulated by epigenetic marks, such as DNA methylation and histone posttranslational modifications, that increase chromatin accessibility and target RAG/RAG2 to V, D and J DNA. It is also dependent on the expression of multiple microRNAs. Mice deficient in Ago2, which is essential for microRNA biogenesis and function, have B cell development blocked at the pro-B cell stage. In agreement with this, B cell specific ablation of microRNA by B cell-specific knockout of Dicer virtually blocks B cell differentiation at the pro-B to pre-B cell transition. After mature B cells encounter antigen, changes of the epigenetic landscape are induced by the same stimuli that drive the antibody response; such epigenetic changes underpin the maturation of the antibody response itself. They instruct those B cell differentiation processes, somatic hypermutation (SHM), class switch DNA recombination (CSR) and plasma cell differentiation, that are central to the maturation of the antibody response as well as differentiation of memory B cells. Inducible histone modifications, together with DNA methylation and microRNAs modulate the transcriptome, particularly the expression of activation-induced cytidine deaminase (AID), central to SHM and CSR, and B lymphocyte-induced maturation protein-1 (Blimp-1), which is central to plasma cell differentiation. Combinatorial histone modifications also function as histone codes in the targeting of the CSR and, possibly, the SHM machinery to the Ig locus by recruiting specific adaptors (histone code readers) that can in turn target and/or stabilize CSR/SHM factors. Epigenetic alterations in memory B cells contribute to their functionally distinction from their naive counterparts. Memory B cells inherit epigenetic information from their precursors and acquire new epigenetic marks, which make these resting B cells poised to promptly respond to antigen. The cross/feedback regulation of different epigenetic modifications/elements further increases the complexity of the B cell epigenome, which interacts with the genetic information for precise modulation of gene expression. It is increasingly evident that epigenetic dysregulation in B cells, including aberrant expression of microRNAs, can result in aberrant antibody responses to microbial pathogens, emergence of pathogenic autoantibodies or B cell neoplastic transformation. Epigenetic marks are potential targets for new therapeutics in autoimmunity and B cell malignancy.